2017
DOI: 10.1007/s12011-017-1117-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Mineral Digestibility, and Blood Characteristics of Ostriches Receiving Drinking Water Supplemented with Varying Levels of Chelated Trace Mineral Complex

Abstract: The effects of water supplementation of chelated trace minerals (CTM, which is named Bonzaplex designed with chelate compounds technology) on growth performance, apparent total tract digestibility (ATTD) of minerals, and some blood metabolites, TM, and antioxidant enzyme values in African ostriches were investigated from 8 to 12 months of age. A total of 20 8-month-old ostriches (five birds in five replicate pens) was randomly allocated into one of the following four treatments: (1) control (basal diet + tap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Because feeding the diet supplemented with 100% of organic TM produced the higher Zn and Mn absorption than the use of 100% of inorganic forms in the current study, it can be said that providing the same levels of organic TM could lead to higher mineral retention. Several researchers have stated the low excretion of organic TM through the excreta and consequently their high retention rate in broilers [6,12], laying hens [25] and growing ostriches [15]. Based on the current results, it appears that lower supplementation of TM to 50% of the commercial level could improve the absorption of TM, without compromising the growth performance of broilers as previously mentioned.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Because feeding the diet supplemented with 100% of organic TM produced the higher Zn and Mn absorption than the use of 100% of inorganic forms in the current study, it can be said that providing the same levels of organic TM could lead to higher mineral retention. Several researchers have stated the low excretion of organic TM through the excreta and consequently their high retention rate in broilers [6,12], laying hens [25] and growing ostriches [15]. Based on the current results, it appears that lower supplementation of TM to 50% of the commercial level could improve the absorption of TM, without compromising the growth performance of broilers as previously mentioned.…”
Section: Discussionsupporting
confidence: 60%
“…A possible reason for this observation is that chelated form of TM may reduce the formation of complexes between P and other metal ions, and, therefore, increase P absorption in the ileum. Another possible reason to explain the greater AID of P might be the improvement in phytate P utilization due to organic acid released from CTM supplement [15], although the mechanism of action is not well-understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the preference of TM sources for poultry feed is based on their cost-bene t ratio, which leads nutritionists to include the least expensive source in diet formulation.However, some previous studies have demonstrated that, when using chelatedTM (CTM), dietary TM concentrations can be decreased because of their high bioavailability [11]. Even though CTM supplementation to broiler feed is not directly related to improved productive performance [6], a single or combination of organic mineralsin poultry feeds has been reported to exert multiple positive effects.For instance, organic TM supplementation resulted in decreased fecal mineralexcretion [9,12], improved bone mineralization and bone size traits [13], higher uric acid and lower blood malondialdehyde (MDA) concentration [1], and improved SOD and GSH-Px activities [14,15]. However, the use of several organic TM, including Fe, Cu, Mn, Zn, Se, iodine (I), and chromium (Cr) synchronously replacing inorganic TM, and what kind of impact they will have on the growth rate and nutritional responses of commercial broiler chickens needs further investigation.…”
Section: Introductionmentioning
confidence: 99%